2008
DOI: 10.1103/physreva.78.020101
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies in electrostatic calibrations for the measurement of the Casimir force in a sphere-plane geometry

Abstract: We have performed precision electrostatic calibrations in the sphere-plane geometry and observed anomalous behavior. Namely, the scaling exponent of the electrostatic signal with distance was found to be smaller than expected on the basis of the pure Coulombian contribution and the residual potential found to be distance dependent. We argue that these findings affect the accuracy of the electrostatic calibrations and invite reanalysis of previous determinations of the Casimir force

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
155
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(168 citation statements)
references
References 26 publications
11
155
2
Order By: Relevance
“…Figure 2c shows that V 0 is measured to be about À 25 mV at small d. Over the full range of distances, V 0 changes by about 15 mV, comparable to previous experiments in the lens-plate 23 and sphere-plate 24 geometries. Even though both the beam and the electrode are made of single-crystal silicon on the same wafer, the residual voltage V 0 is non-zero and shows distance dependence.…”
Section: Resultssupporting
confidence: 68%
“…Figure 2c shows that V 0 is measured to be about À 25 mV at small d. Over the full range of distances, V 0 changes by about 15 mV, comparable to previous experiments in the lens-plate 23 and sphere-plate 24 geometries. Even though both the beam and the electrode are made of single-crystal silicon on the same wafer, the residual voltage V 0 is non-zero and shows distance dependence.…”
Section: Resultssupporting
confidence: 68%
“…In the last few years calibration of the Casimir force measurement setup has attracted considerable interest and even become controversial. [45][46][47][48]52 It was claimed that anomalous dependences of the residual potential difference and separation on contact on the separation distance observed in several experiments cast doubts on the measurements of the Casimir force performed to date. It was also suggested that inasmuch electrostatic calibrations are based on a fitting procedure there is no principal difference detween independent measurements of the Casimir force [20][21][22][23][24][25][26][27][28][29][30][35][36][37][39][40][41][42][43][44]71 and deriving the Casimir force by means of a fit from some much larger measured force of hypothetical origin.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Such dependences were found in several experiments measuring the Casimir force and widely discussed in the literature. [45][46][47][48]52 They are often interpreted as a manifectation of an additional electric force due to the presence of electrostatic surface impurities and space charge effects on the sphere or plate surfaces. In our case, however, these seeming anomalies do not indicate the presence of some extra electric force other than that given by Eqs.…”
Section: Electrostatic Calibrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] It was shown 18 that anomalous behavior of the electrostatic force can be explained due to deviations of the mechanically polished and ground surfaces of centimeter-size lenses from a perfect spherical form. The point is that the typical surface of a centimeter-size lens is characterized in terms of scratch and dig optical surface specification data.…”
Section: Anomalies In Electrostatic Calibrationsmentioning
confidence: 99%